The economics of football - Dobson, Stephen; Goddard, John A. (Cambridge : Cambridge University Press, 2011)
'The second edition of this popular book presents a detailed economic analysis of professional football at club level, with new material included to reflect the development of the economics of professional football over the past ten years. Using a combination of economic reasoning and statistical and econometric analysis, the authors build upon the successes and strengths of the first edition to guide readers through the economic complexities and peculiarities of English club football. It uses a wide range of international comparisons to help emphasize both the broader relevance as well as the unique characteristics of the English experience. Topics covered include some of the most hotly debated issues currently surrounding professional football, including player salaries, the effects of management on team performance, betting on football, racial discrimination and the performance of football referees. This edition also features new chapters on the economics of international football, including the World Cup'--
Includes bibliographical references (p. 423-446) and index.
Keywords: Soccer -- Economic aspects -- Great Britain; Soccer -- Great Britain -- Finance; BUSINESS & ECONOMICS / Economics / Microeconomics